Transformation of Rusty Iron as a TiO₂ Dopant for CO Photodegradation of Jepara Furniture Wooden Oven Exhaust - Syafriyanti Annur; Syarifa Rizka Kautsari; Reysha Camila Iffatul Amalia (Indonesian Scholar Society, 2026)
The furniture industry in Jepara utilizes wood-fired ovens that generate exhaust emissions containing carbon monoxide, which pose potential risks to both the environment and public health. One promising approach to reducing CO emissions is the application of TiO₂ photocatalysts, whose photocatalytic performance can be enhanced through Fe doping using an environmentally friendly Fe source derived from rusty iron waste. TiO₂ photocatalysts can be applied in the form of coatings. This study aimed to analyze the Fe content of rusty iron waste, synthesize and characterize TiO₂-Fe, develop a prototype test chamber for TiO₂-Fe coating application, and evaluate its effectiveness in reducing CO emissions from wood-fired oven exhaust. X-ray fluorescence (XRF) analysis revealed that rusty iron waste contained 99.49% Fe (as total Fe content), demonstrating its suitability as a dopant source for TiO₂-Fe synthesis. TiO₂-Fe was synthesized using Fe:TiO₂ mass ratios of 1:2, 1:1, and 2:1. Scanning electron microscopy (SEM) analysis showed that the 1:1 mass ratio produced smaller particles with a more homogeneous distribution and lower agglomeration, while UV–Vis diffuse reflectance spectroscopy (SR-UV) analysis indicated the greatest reduction in band gap energy, from 3.2 eV to 2.8 eV. Application of the TiO₂-Fe coating in the prototype test chamber achieved a maximum degradation efficiency of 81.8% under visible-light irradiation, outperforming both commercial coatings and TiO₂-FeCl₃ coatings. These findings demonstrate that TiO₂-Fe derived from rusty iron waste has significant potential as a functional photocatalytic material for mitigating air pollution.